(untitled) (University Arena, 2025)
The present paper is an attempt to describe the meaning and function of apologies in sports. Observations have been made on the verbal and non-verbal behavior of athletes in tennis, table tennis, volleyball, billiards etc. On the basis of the analysis made, the universality and the ritual character of the apologies in certain situations, as well as their relation to the sport’s etique tte, are postulated. Their specificity is also outlined in terms of the pragmatic determinants described by Renate Rathmayr: ’the person who caused some damage’; ’the injured person who has suffered harm’; ’the damage itself’.